Efforts for Legal Protection for Customers If Damaged and Loss of Collateral Items Pawned at PT. Pegadaian (Persero) Cikampak Branch - Amal Rejeki Dabutar; Anita Janu Septi; Intan Zuhra; Rinca Eklesia Siringoringo (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this research is to analyze the accountability of PT. Pegadaian (Persero) in the event of damage and loss of mortgage collateral and analyzes the legal remedies that can be taken by the customer in the event of default. Research conducted at PT. Pegadaian (Persero) Cikampak Branch. Methods of data analysis using descriptive qualitative. The results showed that PT. Pegadaian (Persero) Cikampak Branch is responsible in the event of a loss and default experienced by the customer on the collateralized goods as long as the collateral is still under the supervision of the pawnshop. The legal remedy that can be taken is to resolve disputes through deliberation and mediation by providing compensation on the condition that the customer still has a proof of pledge of the pawned goods.